1084 Depression and Stress Generation: Can Sleep Quality Bridge the Gap?. (27th May 2020) - Summers, C; Ciesla, J; Bean, C
Abstract: Introduction: The stress generation literature has established a bidirectional relationship between depression and stress. Not only do stressful life events predict depressive episodes, but a depressive history is also linked to increased, future stressors. One relevant mechanism that has received little attention to account for this relationship is sleep. Sleep difficulties are intertwined with depression, both as a predictive and maintenance factor. Beyond depression, sleep disruption is also a factor in a plethora of stressful events, from an increased risk of automotive accidents to higher reports of interpersonal conflict. The present study explored the role of sleep quality to account for depression's association with stressors. Methods: Ninety-six college students (Age: M = 19.56, SE = .20) reported on their depressive symptoms before undergoing a two-week, online diary, where they reported on sleep quality and the number of stressors experienced. A generalized structural equation model (GSEM) was used to test the relevance of sleep quality to account for baseline depressive symptoms predicting average differences in stressors over the diary. Within the GSEM, a multilevel model was used to explore the daily, within-person association between sleep quality and the number of stressors reported. Results: Baseline depression was predictive of poorer sleep quality ( b = .01, p < .001) and more stressors across the diary ( b = .02, p = .017). Sleep quality mediated the effect of depression on stress generation ( b = .002, p = .036), accounting for 13% of the variance. On a daily level, poorer sleep quality the night before predicted more stressors the next day ( b = .16, p = .027). Conclusion: The results suggest that sleep quality is a relevant mechanism in the prediction of future stressors from depression. Sleep difficulties may represent a pivotal area of future research and intervention target in breaking the cycle between depression and stress generation. Support: Hammen, C. (1991). Generation of stress in the course of unipolar depression. Journal of Abnormal Psychology, 100, 555-561. Tsuno, N., Besset, A., & Ritchie, K. (2005). Sleep and depression. The Journal of Clinical Psychiatry, 66, 1254-1269.